2020
DOI: 10.21203/rs.3.rs-18405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide organization and expression profiling of the R2R3-MYB transcription factor family in sea buckthorn (Hippophae rhamnoides L.)

Abstract: Background MYB transcription factor family involved in multifarious stages of plant growth and development until death, which is one of the largest and most versatile gene families in plants, therefore it is an important regulatory factor in plants. Sea buckthorn (Hippophae rhamnoides L.) is rich in many secondary metabolites and has high nutritional and medicinal value. With the completion of sea buckthorn genome sequencing, it has laid the foundation for us to explore the gene structure, evolutionary relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Among the 42 genes, 45.2% had intron insertions (Fig. 1), a value lower than those of Hippophae rhamnoides (50.6%) [37], maize (60%) [20], and Arabidopsis thaliana (58%) [18], and similar to that of the Sapindaceae Dimocarpus longan (47.3%) [36]. Therefore, we speculate that intron insertion was gradually lost during the evolution of SmUGT s.…”
Section: Gene Structural and Conserved Motifs Of Smugtsmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the 42 genes, 45.2% had intron insertions (Fig. 1), a value lower than those of Hippophae rhamnoides (50.6%) [37], maize (60%) [20], and Arabidopsis thaliana (58%) [18], and similar to that of the Sapindaceae Dimocarpus longan (47.3%) [36]. Therefore, we speculate that intron insertion was gradually lost during the evolution of SmUGT s.…”
Section: Gene Structural and Conserved Motifs Of Smugtsmentioning
confidence: 94%
“…In other species, the expression of UGT genes changes as fruit development progresses. In Hippophae rhamnoides, most UGT genes are expressed at high levels in the early or middle stages of fruit development, and at lower levels in later stages [37]. In peach, 35% of UGT genes have the highest expression level in S1 (the first exponential growth phase, characterized by rapid cell division) [42].…”
Section: Expression Patterns Of Smugt S At Different Stages Of Fruit ...mentioning
confidence: 99%
“…R2R3-MYB (185) transcription factors are reported in the genome of Mangrove, 34 MYB gene are mainly expressed in different tissues (root, leaves), which are related to various stresses (salinity and drought) [35]. Hippophae rhamnoides is the rich source of secondary metabolites, which has economic importance regarding medicinal and nutritional values, 161 R2R3-MYB TFs were obtained through its genome-wide analysis [36]. In a recent study, 111 StR2R3-MYB transcription factors are reported in potato [37].…”
Section: Recent Transcriptomic and Genome-wide Analysis And Expression Of Myb Transcription Factorsmentioning
confidence: 99%